Aplikasi Android Sebagai Media Pembelajaran pada Mata Pelajaran Kimia Kelas XII - Khoirul Nisa; Sutikno Sutikno (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
In the field of education, tutoring is an integral part of the overall educational process. Guidance as part of education has a specific purpose, which is to help individuals develop themselves optimally so that they can find themselves and be able to make choices, decisions and adjustments effectively. Therefore tutoring is very influential in efforts to achieve overall student learning success.